2021
DOI: 10.1051/0004-6361/202039949
|View full text |Cite
|
Sign up to set email alerts
|

The 800 pc long tidal tails of the Hyades star cluster

Abstract: The tidal tails of stellar clusters provide an important tool for studying the birth conditions of the clusters and their evolution, coupling, and interaction with the Galactic potential. The Gaia satellite, with its high-quality astrometric data, opened this field of study, allowing us to observe large-scale tidal tails. Theoretical models of tidal-tail formation and evolution are available. However, the exact appearance of tidal features as seen in the Gaia catalogue has not yet been studied. Here we present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(107 citation statements)
references
References 93 publications
(136 reference statements)
5
102
0
Order By: Relevance
“…Gas expulsion not only unbinds many stars from the clusters, but also decreases their density so that many of the youngest clusters cannot be detected, an idea originally proposed by Lüghausen et al (2012). The overestimate of f IC,pop in older clusters can be caused by neglecting the interaction of clusters with molecular clouds in our models, which probably plays an important role in cluster dissolution (Terlevich 1987;Lamers & Gieles 2006;Chandar et al 2010;Jerabkova et al 2021).…”
Section: Comparison To Observations and To The Current Theoretical Modelmentioning
confidence: 86%
“…Gas expulsion not only unbinds many stars from the clusters, but also decreases their density so that many of the youngest clusters cannot be detected, an idea originally proposed by Lüghausen et al (2012). The overestimate of f IC,pop in older clusters can be caused by neglecting the interaction of clusters with molecular clouds in our models, which probably plays an important role in cluster dissolution (Terlevich 1987;Lamers & Gieles 2006;Chandar et al 2010;Jerabkova et al 2021).…”
Section: Comparison To Observations and To The Current Theoretical Modelmentioning
confidence: 86%
“…Giant molecular clouds passing through a tidal tail can stir asymmetry in the tail (Jerabkova et al 2021), which was indicated in the tail (in this case tail II) of the Hyades (Röser et al 2019). According to the results of Jerabkova et al (2021), giant molecular clouds might distort also tidal tail I so that its tilt β would no longer be a clear function of the age of the cluster or stream.…”
Section: Comparison To Stellar Evolutionary Age Estimatesmentioning
confidence: 94%
“…The combination of the striking precision of the Gaia astrometric measurements and its all sky coverage allowed the detection of prominent structures around some OCs by several groups. , Meingast & Alves (2019) and Jerabkova et al (2021) characterized the tidal tails of the Hyades at large spatial scale with different methods. The tidal tails of Coma Berenices, Ruprecht 147, Praesepe, Blanco 1, NGC 2506 and NGC 752 were discovered successively by Tang et al (2019), Yeh et al (2019), , Zhang et al (2020), Gao (2020) and Bhattacharya et al (2021).…”
Section: Introductionmentioning
confidence: 99%